Cannabis and Psychosis: Are We any Closer to Understanding the Relationship? - Hamilton, Ian (Curr Psychiatry Rep, 2019)
PURPOSE OF REVIEW: This paper provides an update from the literature on understanding of the relationship between cannabis and schizophrenia. In particular, the paper focuses on the latest findings and remaining areas that require investigation. RECENT FINDINGS: Three hypotheses have emerged as potential explanations for the association between cannabis and schizophrenia, namely cannabis can trigger schizophrenia, cannabis is used to mitigate symptoms of schizophrenia, and there are common factors which might account for the association. Biological and genetic factors dominate this field of research; this has been at the expense of exploring social and cultural contributory factors which influence cannabis and schizophrenia. SUMMARY: The evidence for cannabis acting as a causal factor for schizophrenia has so far not been established. Research needs to extend beyond males drawn from western countries if we are to advance knowledge and understanding of the link between cannabis use and schizophrenia.